Contextualising Adab in Islamic Education from the Perspective of Al-Attas - In’ami, Moh; Bambang; Wekke, Ismail Suardi (Journal of Al-Tamaddun, 2025)
This study examines Syed Muhammad Naquib Al-Attas’s distinct approach to Islamic education, focusing on his conceptualization of adab within the educational framework. Character research methods are employed, involving an in-depth review of Al-Attas’ works, alongside relevant literature on his philosophy. This research aims to analyse and articulate Syed Muhammad Naquib Al-Attas’ practical contributions to Islamic educational thought, particularly in the contextualization of adab. The study utilises Paul Recoeur’s hermeneutic method, specifically the processes of distanciation and appropriation, to interpret Al-Attas’ ideas. Findings reveal that Al-Attas perceives each culture as possessing distinct, often irreconcilable, educational values despite their surface-level similarities. Central to Al-Attas’ educational vision, it is found that the contextualisation of adab in his thoughts relates to the purpose of education, focusing on producing a good human being, or in the Islamic tradition referred to as insan kamil.